1993
DOI: 10.3109/07420529309059703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Single-Dose Administration of Naproxen at 10:00 and 22:00 Hours

Abstract: The pharmacokinetics of naproxen was studied in 12 healthy male volunteers after a single oral dose of 500 mg at 10:00 and 22:00 h. Ingestion of drug at 22:00 h delayed the occurrence of peak serum levels (p < 0.0212). None of the other pharmacokinetic parameters exhibited any significant diurnal variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Regarding the Anaprox® formulation, a bioavailability study by Haberer et al (Haberer et al, 2010) and a bioequivalence (BE) study by Setiawati et al(Setiawati et al, 2009) To investigate the bioavailability of naproxen free acid, Rao et al administered 500 mg of pure drug powder filled in hard capsules together with a glass of water to twelve Indian healthy male volunteers, aged between 18 and 22 years, who had fasted overnight. (Rao et al, 1993) In all studies, no concomitant administration of any other drugs was permitted for at least 1 week before the study and food was withheld until 3 hours post-dose.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the Anaprox® formulation, a bioavailability study by Haberer et al (Haberer et al, 2010) and a bioequivalence (BE) study by Setiawati et al(Setiawati et al, 2009) To investigate the bioavailability of naproxen free acid, Rao et al administered 500 mg of pure drug powder filled in hard capsules together with a glass of water to twelve Indian healthy male volunteers, aged between 18 and 22 years, who had fasted overnight. (Rao et al, 1993) In all studies, no concomitant administration of any other drugs was permitted for at least 1 week before the study and food was withheld until 3 hours post-dose.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The performance of the developed PBPK model was verified by simulation of several clinical studies after oral administration and by comparison with the mean observed pharmacokinetic profiles already available in the literature. (Charles and Mogg, 1994;Haberer et al, 2010;Rao et al, 1993;Setiawati et al, 2009;Zhou et al, 1998) Virtual populations were selected to closely match the enrolled individuals in the respective in vivo clinical trials with respect to sample size, ethnicity, gender ratio, and age and weight range. Reported volumes of concomitant liquid intake, dosage form type and sampling schedule were also included in the study design.…”
Section: Verification Of Pbpk Model and Clinical Trial Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The proposed doses of febuxostat for the management of hyperuricemia in gout patients are 80 mg and 120 mg of febuxostat once daily. 15 Although assessment of the chronokinetics of indomethacin and naproxen 35 was not part of the study objectives, the pharmacokinetic data obtained from AM and PM dosing of indomethacin and naproxen provided additional information about the effect of the time of dosing on the pharmacokinetics of indomethacin and naproxen. The chronokinetic data for both indomethacin and naproxen indicate that even though PM dosing compared to AM dosing caused a delay in t max and a slight decrease in C max mean values, AUC 12 mean values were not affected and remained relatively unchanged for both indomethacin and naproxen.…”
Section: Discussionmentioning
confidence: 99%
“…Ollagnier et al (1987) reported that the peak plasma concentration of ketoprofen was twice as high after drug administration at 07 00 h compared with administration at any other time, and t max was much longer after drug administration at 01 00 h compared with 13 00 h. Mustofa et al (1991) and Nagamahender et al (1995) found that the peak serum diclofenac concentration and the AUC value were signi®cantly lower during the night compared with the day. Rao et al (1993)…”
Section: Discussionmentioning
confidence: 99%